“Let's Smash the Idols!” Kemal Pilavoğlu's Sufi Pan-Islamism in Republican Turkey - Dollar, Cathlene (Department of Religious Studies, 2023)
This dissertation is a case-study of a Tijaniyya organization in Turkey and its Turkish founder, Kemal Pilavoğlu (1906-1977), who established the order in or around 1931. The Tijaniyya is a Sufi order from north Africa, founded by Abu al-ʿAbbâs Ahmad ibn Mahammad al-Tijânî (1737–1815) between 1781- 1785. This case-study is grounded in Itzchak Weismann's theory that Sufism in general has played an important role in the Muslim world's response to modernity. This theory underpins the argument that those “Islamists” who continue to be revered as Sufi heroes in Turkey, such as Said Nursi and Necep Fazıl Kisakürek, have drawn on the Ottoman past and the legacy of Islam in their dialogical responses to Mustafa Kemal Atatürk's state-led reform project of modernization during the establishment of Republican Turkey. These Sufi “Islamist” responses to the Kemalist project of forced cultural change, which have been dubbed “Neo-Ottoman” by Hakan Yavuz, successfully resurrected an idealized notion of Ottoman tradition, history, and culture as part of their vision to re-Islamicize Turkish society. Although Pilavoğlu was similarly opposed to Kemalism and the super-imposition of westernization, this dissertation proposes that he did not sufficiently draw upon the Ottoman past in his dialogical response to the rapid modernization of Turkish society vis-à-vis super-imposed European systems of nation-building. Pilavoğlu, in contrast to “Neo-Ottoman” responses, sought to portray a universal notion of Islamic identity which did not vernacularize Islam as an Ottoman-cum-Turkish dimension of cultural identity. Hagiographies written by Pilavoğlu's followers form the data which inform the narrative for this casestudy, and a selection of Pilavoğlu's discursive responses from his extensive body of written work are the focus for analysis. This dissertation also includes summary translations of an assortment of these primary source materials, which have until now not been translated into English.